2005
DOI: 10.1021/jf0402983
|View full text |Cite
|
Sign up to set email alerts
|

Varietal and Interspecific Influence on Micronutrient Contents in Citrus from the Mediterranean Area

Abstract: To specify the genotypic variation of Mediterranean Citrus juices, the contents of carotenoids, flavonoids, and vitamin C were determined by high-performance liquid chromatography. A selection of orange varieties and Mandarin species from the Mediterranean area (Citrus sinensis, Citrus deliciosa Ten, and Citrus clementina Hort. ex Tan) was evaluated using carotenoid profiles and flavanones contents. Among the eight varieties of orange (Salustiana, Hamlin, Shamouti, Pera, Valencia, Maltaise, Sanguinelli, and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
161
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(179 citation statements)
references
References 27 publications
13
161
2
3
Order By: Relevance
“…Total phenolic compounds determined as the sum of individual compounds ranged from 308.06 AE 30.62 to 476.10 AE 26.10 mg/L, with the highest amounts being recorded in SV variety. These results are in agreement with those reported in OJs from different varieties (Dhuique-Mayer et al, 2005;Kebelek et al, 2009;Rapisarda et al, 2008).…”
Section: Phenolic Compounds and Ascorbic Acidsupporting
confidence: 93%
See 2 more Smart Citations
“…Total phenolic compounds determined as the sum of individual compounds ranged from 308.06 AE 30.62 to 476.10 AE 26.10 mg/L, with the highest amounts being recorded in SV variety. These results are in agreement with those reported in OJs from different varieties (Dhuique-Mayer et al, 2005;Kebelek et al, 2009;Rapisarda et al, 2008).…”
Section: Phenolic Compounds and Ascorbic Acidsupporting
confidence: 93%
“…The AscA contents of Valencia varieties ranged from 42.52 to 63.30 mg/100 mL, in accordance with other studies which reported 45-64 mg/100 mL (Dhuique-Mayer et al, 2005;Rapisarda et al, 2008).…”
Section: Phenolic Compounds and Ascorbic Acidsupporting
confidence: 90%
See 1 more Smart Citation
“…Carotenoids were analyzed according to an already published method [22]. The residue was dissolved in 1 mL [dichloromethane:tertmethyl-buthyl-ether:methanol] (50:40:10, v/v/v).…”
Section: Carotenoid Analysismentioning
confidence: 99%
“…With regard to chemical composition, orange is typically considered as one of the products with high contents of antioxidants and vitamins (Del Caro et al, 2004;Dhuique-Mayer et al, 2005). It is well known that the intake of antioxidant compounds is associated with the prevention of various human oxidative stress-related diseases such as neurodegenerative and cardiovascular diseases, stroke, cataractogenesis, diabetes and cancer (Halliwell, 2011;Mateos et al, 2005;Schreckinger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%